Analysis of the variance water distribution of pivot sprinkler irrigation on the productivity of the potato plant in El Oued region of Algeria - Messaoudi Mohammed; Hacene Laouedj; Ghemam Amara Djilani (Edirne. Turkiye, 2023)
This study aimed to determine the extent different of distribution of the axial sprinkler water as a method of irrigation, and the effect of this on the quantity and quality of potato plant production in different areas along the axis sprinkler in the sandy soil of Eloued region in Algeria. For this, we relied on a sample of data consisting of 150 observations distributed over 10 areas according to the length of the axis. statistically we used oneway-analysis of variance after ensuring its statistical validity. Accordingly, we concluded that despite the significant statistical significance of the difference in the distribution of irrigation water( and the time taken and flow strength) along the axis, the difference in the amount of water supplied in the tenth area (tail region) reached a maximum of 57,58 % relative to the reference area ( the fourth region), which recorded at 42,42 % of what the reference area obtained, and at least 21,60 % was obtained in the eighth area relative to the reference region, which obtained 78,40 % of what the reference area obtained. However, according to the tests of our study, this had no significant effect on the difference, quantity and quality of production along the radius at the 5 % level. In light of these results, we concluded that the productivity of the irrigation water component fundamentally differs between the areas along the axis, which means that this irrigation method is not economical in sandy soils.
Intervention
Keywords: axial irrigation; potato production; the analysis of variance; sandy soil